HARDWARE IMPLEMENTATION OF ITB GANESHA CAMPUS SOLID WASTE MONITORING SYSTEM - Morteza Mudrick, Muhammad
The monitoring of temporary waste disposal sites (TPSS) is one of the issues in waste management at ITB Ganesha campus. Waste collectors currently perform manual checking to determine the level of waste in TPSS. This leads to waste piling up and inefficient waste collection routes and time wastage. To address this problem, we have developed a waste monitoring system. The developed system detects the fill level of waste bins and sends this data to the waste collection personnel. The author's contribution focuses on the hardware component of the waste monitoring system. The hardware consists of an ESP8266 microcontroller and 3 HC SR04 ultrasonic sensors, powered by a 4500mAh lithium-ion battery. The system detects the distance to the surface of the waste bin using ultrasonic sensors. The data is processed by the ESP8266 to determine the waste bin's fill level category. Then the data is transmitted to a database and a web app for display to the waste collection personnel. Additionally, an access point feature is implemented to allow device configuration. The implementation results show that the system has a maximum error of less than 5% in tests conducted on flat surfaces. Moreover, theoretically, the system can operate for up to 14 days with a 4500mAh battery. Future improvements can be made in power management, physical system design, and more comprehensive testing.